2019
DOI: 10.1055/a-1031-9327
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse endoscopically visible, predominantly low grade dysplasia in Barrett’s esophagus (with video)

Abstract: Background  Low grade dysplasia (LGD) in Barrett’s esophagus (BE) has generally been considered as undetectable endoscopically. Aim  To describe a phenotype which consists of diffuse, endoscopically visible, predominantly low grade dysplasia in Barrett’s esophagus (DEVLB), with often subtle but visible endoscopic changes seen with high definition white light (HDWL) and narrow-band imaging (NBI). Method  A systematic search of a prospectively collected database for patients satisfying predefined criteria for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
0
4
1
Order By: Relevance
“…This was considerably lower than the 50.4% of visible LGD lesions identified at BRU assessment (in the same cohort). Our high proportion of visible lesions was also significantly more than the current reported rates from other expert Barrett's centres (6.4 -18.7%) [7,8,9,10,19,20].…”
Section: Discussioncontrasting
confidence: 48%
See 3 more Smart Citations
“…This was considerably lower than the 50.4% of visible LGD lesions identified at BRU assessment (in the same cohort). Our high proportion of visible lesions was also significantly more than the current reported rates from other expert Barrett's centres (6.4 -18.7%) [7,8,9,10,19,20].…”
Section: Discussioncontrasting
confidence: 48%
“…The majority of non-visible lesions detected on protocol biopsies had a single, <1mm focus of LGD, whilst visible LGD lesions often had multiple foci or a larger, continuous area of LGD within the biopsy or resection specimen. Furthermore, our patients with the DEVLB phenotype [10] frequently had LGD that was deeper than 1mm (see Figure 9) and interestingly did not respond to RFA therapy (the reported controlled treatment depth of RFA is 0.5-1mm [23]).…”
Section: Accepted Manuscriptmentioning
confidence: 81%
See 2 more Smart Citations
“…The 50% rate of visible LGD reported by He et al is much higher than the 6% to 19% reported in other Barrett's expert centers. It can be explained by the systematic use of a cap to analyze the Barrett's segment, the specific expertise of the group in analyzing the Barrett's mucosa, demonstrated by the description in 2019 of the diffuse endoscopically visible LGD in BE or DEVLB [4], and the performances in diagnostic endoscopy of the community centers involved. However, the fact that LGD is endoscopically invisible in half of the cases, even to experts specifically seeking it, reminds us that random biopsies following the Seattle protocol are still needed in 2023.…”
mentioning
confidence: 99%